INTEREST IN LEARNING ENGLISH STUDENTS THROUGH AUDIO VISUAL MEDIA IN SMKS GENERUS BANGSA - Mhd Arief Qamara; Mhd Putra Gama; Ricky Dian Saputra; Emeliya Sukma Dara (Universitas Maritim AMNI Semarang, 2023)
This study aims to determine the interest and quality of the English teaching and learning process of students, especially in listening skills. Knowing interests is carried out through the use of audio-visual media with role-playing methods that are expected to provide opportunities for the creation of pleasant learning conditions. Thisclass obtained optimal results where students who were interested in taking English lessons could increase significantly. This research is in the form of Class Action Research which is carried out using VCD media, which consists of four stages: planning, implementing actions, observation, and reflection. Actions can be done by applying learning with audio-visual media and continued with role-playing methods. This research was conducted on 11 students of class X 1 SMKS Generus Bangsa. Responses to the progress of student interest are obtained from the results of student questionnaires, student interviews, student learning logs, observations, interviews between teachers, teacher journals, daily test results and assignments. Instrument validation is carried out with critical reflection between research teachers and face validity. Data validation is carried out by triangulating observations from the aspects of students, teachers and partner teachers. The results of each cycle reflection are used to plan further steps.